Interaction of pathogens with the endothelium - Hippenstiel, Stefan; Suttorp, Norbert (Thrombosis and Haemostasis, 2003)
The endothelium lines the inner surface of the vessel wall establishing a multifunctional, semi-permeable cellular barrier at blood-tissue interface. The large total surface of the endothelium is exposed to pathogens, pathogen-derived products as well as to agents of the activated host defense during an inflammatory reaction. The endothelium is not only specifically targeted by important infective agents like Rickettsiae (1) or Bartonella (2), it is involved in virtually most, if not all, acute inflammatory responses. Pathogens attack the endothelium by a wide variety of strategies, as different as activation of preformed receptor-mediated pathways in the endothelium, release of pore-forming exotoxins or intracellular replication and chronic parasitism. These pathophysiological forces affect the endothelial phenotype, resulting in endothelial barrier dysfunction, increased leukocyte-endothelial interaction, mediator release, and procoagulant activity. Moreover, endothelial responses retroact on the invading pathogen as well as on the host defense resulting in a complex and dynamic interaction (Fig. 1). Endothelial activation contributes considerably to inflammation and resulting clinical characteristics. In this context the endothelium is not just a passive victim, it rather aggravates the ongoing struggle with the pathogen. In this review we focus on some important mechanisms of the cellular microbiology of endothelial infection by bacteria and viruses.
Keywords: Endothelium; infection; inflammation; bacteria; virus